Pengaruh Budaya Organisasi dan Digitalisasi terhadap Kinerja Pegawai Lembaga Regulator Sektor Keuangan: Studi Perilaku Ekonomi dalam Pengambilan Keputusan - M Khufron; Sitti Rakhman (Jaringan Pemberdayaan Politik Lingkungan Hidup, 2025)
Financial regulatory institutions play a strategic role in maintaining the stability and integrity of both national and global financial systems. In the face of digital-era challenges and structural shifts, improving employee performance has become a primary focus to ensure institutional effectiveness. This study aims to explore the influence of organizational culture and digital transformation on employee performance, and how these two factors affect decision-making patterns from a behavioral economics perspective. Using a descriptive qualitative approach based on secondary data, this study analyzes official documents, academic publications, and reports from financial regulators in various countries. The findings reveal that an integrity- and collaboration-based organizational culture, along with structured implementation of digitalization, can enhance work efficiency, decision accuracy, and employee adaptability. This study is expected to serve as a reference for strategic human resource management in the public sector.